Effects of basalt powder and silica fume on ultra-high-strength cementitious matrix: A comparative study. (December 2022) - Shen, Manlin; Zhou, Lixiao; Chen, Zuyong; Shen, Yinong; Huang, Botao; Lv, Jianfu
Abstract: Understanding the effects of basalt powder on the microstructures and hydration products of ultra-high-strength cementitious matrices (UHSCMs) can contribute to the application of basalt powder in ultra-high-performance concrete. This study assesses the effects of basalt powder and silica fume on cementitious matrices by strength examination, microstructure analysis, and material characterization. The results prove the feasibility of adding basalt powder to UHSCMs. Both basalt powder and silica fume can function as reactive additives for cementitious matrices and improve silicate polymerization in calcium silicate hydrate (C-S-H) gels. The calcium-enrichment of the cementitious matrices containing basalt powder leads to the decalcification of the C-S-H structure, the refinement of the pore structure, and the decrease in the strength of UHSCMs. Moreover, a high-temperature curing procedure can alleviate the above adverse effects of basalt powder on the strength of cementitious matrices. The findings of this study are useful for improving the sustainability of concrete materials with high and ultra-high performance.